The Inside of the Cup $1 (BVolume 08s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Inside of the Cup $1 (BVolume 08" by Winston Churchill is a novel published in 1913. When Reverend John Hodder arrives at an elite urban church, he's expected to preach a comfortable Christianity that won't disturb the wealthy congregation. But his growing awareness of poverty and corruption triggers a spiritual crisis that transforms his ministry. His radical new preaching sparks a fierce battle between church traditionalists and reformers, threatening his career while igniting a nationwide debate about faith's role in modern American life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Inside_of_the_Cup
Release date is 2004-10-17
Produced by David Widger
Keywords: Christian life -- Fiction; Attitude change -- Fiction; Christian ethics -- Fiction; Conscience -- Religious aspects -- Fiction